Gallstone obstruction at the proximal ileum in an elderly woman: CT findings - Francesco Messina; Carmela Tebala; Grazia Calabrese; Lorena Turano; Maria Giovanna Fava; Nicola Arcadi (Radiology Case Reports, 2021)
We present the case of a 73 years old woman with intestinal obstruction caused by a rare cause of biliary ileus, who arrived at our emergency department with lower abdominal quadrants pain (since about 2 months), recently associated with nausea, vomiting and abdominal distension. After clinical and laboratory evaluations, a computed tomography (CT) scan without intravenous contrast medium administration was urgently requested. CT had shown the presence of a large gallstone (diameter of about 6 cms) at the proximal ileum (stopped in this tract after the passage through a biliary-enteric fistula), and another gallstone (diameter of about 2 cms) in the gallbladder, associated with concentric thickening of gallbladder's walls, gas in the biliary tree, obliteration of peri-gallbladder's fat density and fluid in the peri-subhepatic area. The patient had urgently a surgical treatment (videolaparoscopy). CT had a crucial role for the diagnosis of intestinal obstruction, for its high sensitivity and specificity. It is well able to provide the causes and the level of the obstruction, its extension and complications, thus orienting toward the best clinical management/outcome for the patient.